In vitro site selection of a consensus binding site for the Drosophila melanogaster Tbx20 homolog midline. - Nima Najand; Jae-Ryeon Ryu; William J Brook (PLoS ONE, 2012)
We employed in vitro site selection to identify a consensus binding sequence for the Drosophila melanogaster Tbx20 T-box transcription factor homolog Midline. We purified a bacterially expressed T-box DNA binding domain of Midline, and used it in four rounds of precipitation and polymerase-chain-reaction based amplification. We cloned and sequenced 54 random oligonucleotides selected by Midline. Electromobility shift-assays confirmed that 27 of these could bind the Midline T-box. Sequence alignment of these 27 clones suggests that Midline binds as a monomer to a consensus sequence that contains an AGGTGT core. Thus, the Midline consensus binding site we define in this study is similar to that defined for vertebrate Tbx20, but differs from a previously reported Midline binding sequence derived through site selection.